"Spontaneous" medication‐related osteonecrosis of the jaw; two case reports and a systematic review. (9th September 2018) - Khominsky, A; Lim, MAWT
Abstract: Medication‐related osteonecrosis of the jaw (MRONJ) is a severe adverse drug effect consisting of bone destruction of the maxilla and/or mandible. The most common precipitating event described in the literature is the extraction of a tooth followed by "spontaneous" occurrence with no clear predisposing event. Current studies are investigating methods of managing dental extractions in patients at risk of MRONJ; however, no studies to date examine the aetiology and management of "spontaneous" MRONJ. This paper describes two cases of "spontaneous" MRONJ seen at the Dental Unit in the Alfred Hospital and systematically reviews the current literature. No significant interactions ( P  >   0.05) were detected between variables: age, sex, bone disease, antiresorptive, antiresorptive duration, jaw, location and stage. "Spontaneous" cases were commonly associated with the mylohyoid ridge, palatal tori and other anatomical sites, and tended to occur in those generally considered at low risk of developing MRONJ. The review suggests that perhaps the term "spontaneous" is a misnomer and thorough history taking is critical in establishing a precipitating event.